Effect of water confidence activity on participants’ self-preparation in whitewater rafting activity - Ali, Siti Fadhilah (2019)
Whitewater rafting activity is fast gaining popularity alongside with other adventure tourism activities. However, participants are exposed to accident, injury, and even death when doing whitewater rafting activity. Hence, self-preparation is essential to reduce risks and ensuring safe completion of the activity. The present study utilizes the quasi experimental design to compare participants’ self-preparation before and after participating in whitewater rafting activity. It also determines the effect of water confidence activity on participants’ self-preparation in whitewater rafting activities. Among the mental, physical and emotion preparation, mental preparation records the highest mean score. Significant differences were observed between the mean scores before and after participating in the activity. Mental preparation contributes the highest percentage in water confidence activity. The findings show that mental preparation is the most important variable in self-preparation.